Microsoft C/C++ version 7.0 : (Microsoft corporation, 1991)
This book introduce about the microsoft foundation class library tutoral: using the Microsoft foundation class libra tutorial, creating programming with the Microsoft foundation. The Microsoft foundation class library cookbook...